Healing of chronic wounds at the remodeling stage: the ratio of hormonal and immune parameters - S.B. Pavlov; N.M. Babenko; M.V. Kumetchko; O.B. Litvinova; I.V. Komarchuk; I.O. Kudrevych (Медицина неотложных состояний)
Background. Both patients and healthcare systems around the world experience the negative consequences of chronic wounds. Chronic wounds often precede serious events such as amputation and premature death. Objective: to study the relationship between endocrine factors (insulin and cortisol) and bioactive molecules (interferon-γ (IFN-γ) and transforming growth factor-β1 (TGF-β1)), influencing the development of reparative processes of chronic wounds at the remodeling stage in an experiment, and to analyze the features of the histostructure of rat skin in the area of chronic wound healing. Materials and methods. The study was conducted on 12 white rats. Animals were randomized into intact and experimental groups, with 6 participants in each group. Chronic wounds were induced in the experimental group. Rats were euthanized on the 28th day of the experiment. In the blood serum, the insulin, cortisol, IFN-γ, and TGF-β1 levels were determined by enzyme immunoassay. Histological examination was carried out using generally accepted methods. Results. It was shown that the concentrations of insulin, cortisol, and TGF-β1 in animals of the experimental group were almost doubled compared to intact rats. The level of IFN-γ in animals with wounds was 1.2 times lower than in intact rats. Microscopic examination showed that the wounds were at the stage of remodeling. At the same time, signs of inflammation are partially preserved, which may indicate chronicity of the reparative process. Conclusions. Understanding the mechanisms of reparative processes during wound healing will allow for the development of clinical protocols to improve care for patients with injuries.